Clinical characteristics of PD patients with LRRK2 G2385R and R1628P variants. (15th October 2018) - Liang, Dongxiao; Shu, Li; Pan, Hongxu; Xu, Qian; Guo, Jifeng; Yan, Xinxiang; Tang, Beisha; Sun, Qiying
Highlights: a large sample of 721 PD patients of Chinese origin. motor symptoms, non-motor symptoms and co-morbidities were analyzed in our study. the relationship between the variants and clinical symptoms were analyzed. Abstract: LRRK2 is the most common genetic cause of PD. G2385R and R1628 P variants are the most common variants of LRRK2 in Chinese populations. Consensus on the clinical features of G2385R and R1628 P related PD has not been reached yet, although it had been widely studied. In our study, genotype analyses were conducted on 721 PD patients of Chinese origin. A total of 62 G2385R carriers, 32 R1628 P carriers and 623 idiopathic PD patients underwent the following clinical feature analysis. Motor symptoms, non-motor symptoms and co-morbidities were the targeted features to be analyzed. As a result, Neither the G2385R nor the R1628 P carriers showed significant clinical feature differences when compared to the idiopathic PD patients, so did the comparison between the G2385R and the R1628 P carriers. In conclusion, the clinical features of PD patients with LRRK2 G2385R or R1628 P variants were similar to those of idiopathic PD.